2021
DOI: 10.1038/s41467-021-23333-3
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and lung resident memory T cell responses against SARS-CoV-2

Abstract: Resident memory T cells (TRM) positioned within the respiratory tract are probably required to limit SARS-CoV-2 spread and COVID-19. Importantly, TRM are mostly non-recirculating, which reduces the window of opportunity to examine these cells in the blood as they move to the lung parenchyma. Here, we identify circulating virus-specific T cell responses during acute infection with functional, migratory and apoptotic patterns modulated by viral proteins and associated with clinical outcome. Disease severity is a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
142
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 73 publications
(135 reference statements)
6
142
0
Order By: Relevance
“…More recently it has been demonstrated that lung CD4 + and CD8 + Trm were present in SARS-CoV-2-infected patients and reduced disease severity was shown to be associated with increased numbers of airway CD4 + and CD8 + Trm 104 , 105 . These Trm cells produced IFNγ upon in vitro stimulation and importantly persisted for at least 10 months in convalescent patients 104 , 106 . Although less is known about SARS-CoV-2-specific Trm, it has been reported that the depletion of CD8 + T cells in non-human primates prior to re-challenge with SARS-CoV-2 resulted in elevated viral titers in the nasal tissue, which may indicate a role for nasal CD8 + Trm in protection 107 .…”
Section: The Protective Capacity Of Respiratory Tract Trmmentioning
confidence: 97%
“…More recently it has been demonstrated that lung CD4 + and CD8 + Trm were present in SARS-CoV-2-infected patients and reduced disease severity was shown to be associated with increased numbers of airway CD4 + and CD8 + Trm 104 , 105 . These Trm cells produced IFNγ upon in vitro stimulation and importantly persisted for at least 10 months in convalescent patients 104 , 106 . Although less is known about SARS-CoV-2-specific Trm, it has been reported that the depletion of CD8 + T cells in non-human primates prior to re-challenge with SARS-CoV-2 resulted in elevated viral titers in the nasal tissue, which may indicate a role for nasal CD8 + Trm in protection 107 .…”
Section: The Protective Capacity Of Respiratory Tract Trmmentioning
confidence: 97%
“…SARS-CoV-2 infection induces a virus-specific T cell immunity that can be detected at least 8 months after infection in peripheral blood, but analyses on tissue samples are scarce. Recently, preliminary studies on lung and nasal tissue obtained from SARS-CoV-2 convalescent individuals have found T RM responses with functional reactivity against several SARS-CoV-2 proteins that persist for at least 2 to 10 months after infection [ 112 , 113 ]. Virus-specific T RMs located in the upper respiratory tract are known to be long-lived [ 114 ], but further studies are required to determine the longevity of SARS-CoV-2-specific T RMs in the lower respiratory tract, given that studies in mice have demonstrate their gradual loss in the lung [ 115 ].…”
Section: Memory T Cells In Tissuesmentioning
confidence: 99%
“…Indeed, delayed or insufficient activation of T cell responses may lead to severe lung damage or systemic inflammation, whereas early induction of functional SARS-CoV-2-specific T cells is associated with rapid viral clearance and mild disease in COVID-19 patients [ 448 , 449 , 450 ]. In agreement with analyses in the blood, functional and consistent CD8 + resident-memory (TRM) and CD4 + T-helper-17 (TH17) cells in bronchoalveolar lavages were associated with beneficial outcomes [ 451 , 452 ]. Both CD4 + and CD8 + T cell responses to SARS-CoV-2 have been determined as important parameters associated with control of SARS-CoV-2 infection, yet CD4 + T cell responses appear even more prominent than CD8 + T cell responses [ 221 , 443 , 444 , 453 ].…”
Section: Cellular Responsesmentioning
confidence: 53%